Editorial Essay: Iraqi Refugees, Beyond the Urban Refugee Paradigm - Chatelard, Géraldine; Morris, Tim (Refuge: Canada’s Journal on Refugees, 2012)
Displacement and exile have been recurrent and durable phenomena affecting Iraqi society for the last 90 years. The process of forming an Iraqi state from the ruins of the Ottoman empire, which Aristide Zolberg has analyzed as a prime factor generating refugee flows, has been ongoing since 1920. Unfinished endeavours to build a state and nation have been characterized by almost incessant antagonistic claims over the nature of the state and national identity, the exercise of and access to political power, control of natural resources and border sovereignty. Political repression, violent regime change, redefinition of national identity, demographic engineering, and domestic or international armed conflicts have resulted in eviction, deportation, denaturalization, political emigration, and flight from violence. A large part of displacement in Iraq has been internal. But vast numbers of refugees and exiles have also formed a regional and global diaspora extending from Iran, Jordan, Israel, Syria, all the way to such distant emigration countries as New Zealand.